The answer is that f-1(3) = 7.
In order to find the answer, we first must find the inverse function. The f-1 indicates that we are looking for an inverse. To find any inverse, we first must switch the x and f(x) values. We then solve for the new f(x), which gives us the inverse.
f(x) = (2x - 2)/4 ----> Switch x and f(x)
x = (2f(x) - 2)/4 -----> Multiply both sides by 4
4x = 2f(x) - 2 ----0-> Add 2 to both sides
4x + 2 = 2f(x) ------> Divide both sides by 2
f-1(x) = (4x + 2)/2
Now that we have the inverse function, we can put in 3 and find the answer.
f-1(x) = (4x + 2)/2
f-1(3) = (4(3) + 2)/2
f-1(3) = (12 + 2)/2
f-1(3) = (14)/2
f-1(3) = 7